ISOLATION OF PHYTOCONSTITUENT, IN VITRO ANTICANCER STUDY IN HELA AND MCF-7 CELL LINES AND MOLECULAR DOCKING STUDIES OF POTHOS SCANDENS LINN - NAIR, SEEMA S.; VARKEY, JOYAMMA (International Journal of Current Pharmaceutical Research, 2021)
Objective: This study aims to isolate an active phytoconstituent from ethanolic leaf extract of Pothos scandens Linn., to evaluate in vitro anticancer activity, and to carry out molecular docking studies of the isolated phytoconstituent. Methods: The bioactive constituent 1,1’-(4,5-dihydroxy benzene-1,2-diyl) bisoct-7-en-1-one, a phenolic compound, was isolated by using chromatographic methods and the structure was elucidated by various spectroscopic techniques. In vitro anticancer activity was evaluated against HeLa and MCF 7 cell lines. The viability of cells was evaluated by direct observation of cells by an Inverted phase-contrast microscope and by the MTT assay method. IC50 was calculated using the linear regression model. Results: The results of anticancer studies revealed that different concentrations of the ethanolic extract of leaves of Pothos scandens Linn. exhibited cytotoxic activity against HeLa and MCF 7 cell lines with IC50 of 22.9 and 18.32 μg/ml, respectively. The anticancer potential of the plant was revalidated by in silico molecular docking study with Vascular Endothelial Growth Factor Receptor 2 (VEGFR2, PDB ID: 4AG8) using Discovery studio 2018. Results of the docking study showed that the ligand exhibited strong interaction with the VEGFR2 kinase with significant binding energy. Conclusion: Pothos scandens linn. can be used for the isolation of potent anticancer agents.